Left-sided cecal diverticulitis associated with midgut malrotation - Jia-Hui Chen (Tzu Chi Medical Journal)
Malrotation of the midgut is generally considered as a pediatric pathology with the majority of patients presenting in childhood. The diagnosis is rare in adults, which sometimes leads to delay in diagnosis and treatment. An index of suspicion is therefore required when dealing with patients of any age group with abdominal symptoms. We present a case of a 26-year-old male who presented with left lower abdominal pain with preoperative computed tomography showing suspected left-sided appendicitis associated with midgut malrotation. The duodenum, small bowel, and cecum were abnormally located, with the presence of a thickened and inflamed appendix with fecalith images. The patient underwent an emergency laparotomy, and ruptured cecal diverticulitis with abscess formation was confirmed. We performed a cecectomy, and the patient did not have an uneventful postoperative recovery. A review of the literature is presented to highlight the rarity of midgut malrotation and the controversies surrounding its surgical management in the adult population with ruptured left-sided cecal diverticulitis.